1985
DOI: 10.1017/s0021859600043215
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Litchi chinensis seeds when stored in air and in water

Abstract: India is the second largest litchi producing country in the world after China (Syamal & Mishra, 1984), yet the number of litchi cultivars grown in the country is quite small compared with mango (Mangifera indica). In mango most of the choicest Indian cultivars have been obtained from chance seedlings (Singh, 1960) grown in the past without any definite aim in mind. Litchi, as a result of crosspollination (Chaturvedi, 1965), is a highly heterozygous fruit, and as such, its seedlings, like those of mango, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…1973) Roberts et al (1984) also claimed that the most promising method of germplasm conservation for recalcitrant seeds is storage in liquid nitrogen Berjak et al (1989) suggested that the germplasm of recalcitrant seeds could be conserved by cryopreservation of their excised embryo If embryonic axes have been desiccated to around 20% moisture content without loss of viability, it is possible that cooling and storage in liquid nitrogen will be achieved more easily This implies that, if seeds with higher desiccation tolerance can be obtained, cryopreservation will more easily be achieved Lychee seeds at different developmental stages differ in desiccation tolerance (Xia et al, 1990, which encouraged us to investigate the relation between seed development and desiccation tolerance Lychee (Litchi chinensis Sonn ) seed is recalcitrant (Hanson, 1984) and viability is completely lost when seeds are dried under open conditions at around 30 C for 4 days Ray and Sharma (1985) reported that Litchi chinensis can be stored in water for 15 days with a final 75% germination The viability of Clausena lansium (wampee) seeds was less than 50% when seeds were placed under open condition for 6 days and the moisture content decreased to 33-35% (Fu et al 1989a,b) Hoffmann andSterner (1989) also reported recalcitrance of wampee seeds Lychee and wampee are economically important fruit trees native to South China Overcoming their recalcitrance would be valuable for agricultural practice and germplasm conservation 1973) Roberts et al (1984) also claimed that the most promising method of germplasm conservation for recalcitrant seeds is storage in liquid nitrogen Berjak et al (1989) suggested that the germplasm of recalcitrant seeds could be conserved by cryopreservation of their excised embryo If embryonic axes have been desiccated to around 20% moisture content without loss of viability, it is possible that cooling and storage in liquid nitrogen will be achieved more easily This implies that, if seeds with higher desiccation tolerance can be obtained, cryopreservation will more easily be achieved Lychee seeds at different developmental stages differ in desiccation tolerance (Xia et al, 1990, which encouraged us to investigate the relation between seed development and desiccation tolerance Lychee (Litchi chinensis Sonn ) seed is recalcitrant (Hanson, 1984) and viability is completely lost when seeds are dried under open conditions at around 30 C for 4 days Ray and Sharma (1985) reported that Litchi chinensis can be stored in water for 15 days with a final 75% germination The viability of Clausena lansium (wampee) seeds was less than 50% when seeds were placed under open condition for 6 days and the moisture content decreased to 33-35% (Fu et al 1989a,b) Hoffmann andSterner (1989) also reported recalcitrance of wampee seeds Lychee and wampee are economically important fruit trees native to South China Overcoming their recalcitrance would be valuable for agricultural practice and germplasm conservation…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1973) Roberts et al (1984) also claimed that the most promising method of germplasm conservation for recalcitrant seeds is storage in liquid nitrogen Berjak et al (1989) suggested that the germplasm of recalcitrant seeds could be conserved by cryopreservation of their excised embryo If embryonic axes have been desiccated to around 20% moisture content without loss of viability, it is possible that cooling and storage in liquid nitrogen will be achieved more easily This implies that, if seeds with higher desiccation tolerance can be obtained, cryopreservation will more easily be achieved Lychee seeds at different developmental stages differ in desiccation tolerance (Xia et al, 1990, which encouraged us to investigate the relation between seed development and desiccation tolerance Lychee (Litchi chinensis Sonn ) seed is recalcitrant (Hanson, 1984) and viability is completely lost when seeds are dried under open conditions at around 30 C for 4 days Ray and Sharma (1985) reported that Litchi chinensis can be stored in water for 15 days with a final 75% germination The viability of Clausena lansium (wampee) seeds was less than 50% when seeds were placed under open condition for 6 days and the moisture content decreased to 33-35% (Fu et al 1989a,b) Hoffmann andSterner (1989) also reported recalcitrance of wampee seeds Lychee and wampee are economically important fruit trees native to South China Overcoming their recalcitrance would be valuable for agricultural practice and germplasm conservation 1973) Roberts et al (1984) also claimed that the most promising method of germplasm conservation for recalcitrant seeds is storage in liquid nitrogen Berjak et al (1989) suggested that the germplasm of recalcitrant seeds could be conserved by cryopreservation of their excised embryo If embryonic axes have been desiccated to around 20% moisture content without loss of viability, it is possible that cooling and storage in liquid nitrogen will be achieved more easily This implies that, if seeds with higher desiccation tolerance can be obtained, cryopreservation will more easily be achieved Lychee seeds at different developmental stages differ in desiccation tolerance (Xia et al, 1990, which encouraged us to investigate the relation between seed development and desiccation tolerance Lychee (Litchi chinensis Sonn ) seed is recalcitrant (Hanson, 1984) and viability is completely lost when seeds are dried under open conditions at around 30 C for 4 days Ray and Sharma (1985) reported that Litchi chinensis can be stored in water for 15 days with a final 75% germination The viability of Clausena lansium (wampee) seeds was less than 50% when seeds were placed under open condition for 6 days and the moisture content decreased to 33-35% (Fu et al 1989a,b) Hoffmann andSterner (1989) also reported recalcitrance of wampee seeds Lychee and wampee are economically important fruit trees native to South China Overcoming their recalcitrance would be valuable for agricultural practice and germplasm conservation…”
Section: Introductionmentioning
confidence: 99%
“…Recalcitrant seeds cannot tolerate desiccation (Roberts. 1973) Roberts et al (1984) also claimed that the most promising method of germplasm conservation for recalcitrant seeds is storage in liquid nitrogen Berjak et al (1989) suggested that the germplasm of recalcitrant seeds could be conserved by cryopreservation of their excised embryo If embryonic axes have been desiccated to around 20% moisture content without loss of viability, it is possible that cooling and storage in liquid nitrogen will be achieved more easily (Fu et al, 1993) This implies that, if seeds with higher desiccation tolerance can be obtained, cryopreservation will more easily be achieved Lychee seeds at different developmental stages differ in desiccation tolerance (Xia et al, 1990(Xia et al, , 1993, which encouraged us to investigate the relation between seed development and desiccation tolerance Lychee (Litchi chinensis Sonn ) seed is recalcitrant (Hanson, 1984) and viability is completely lost when seeds are dried under open conditions at around 30 C for 4 days Ray and Sharma (1985) reported that Litchi chinensis can be stored in water for 15 days with a final 75% germination The viability of Clausena lansium (wampee) seeds was less than 50% when seeds were placed under open condition for 6 days and the moisture content decreased to 33-35% (Fu et al 1989a,b) Hoffmann andSterner (1989) also reported recalcitrance of wampee seeds Lychee and wampee are economically important fruit trees native to South China Overcoming their recalcitrance would be valuable for agricultural practice and germplasm conservation…”
Section: Introductionmentioning
confidence: 99%
“…It was recommend the storage in a refrigerator a way to reduce the speed of loss of viability. Ray & Sharma (1985), Menzel (1985) and Chen & Fu (1989) reported that lychee seeds were viable for only 4 -5 days.…”
Section: Resultsmentioning
confidence: 99%